Digital Literasi dan Self Directed Learning dalam Pembelajaran Mahasiswa PBI IAIN Surakarta - Khoirul Latifah (Academica: Journal of Multidisciplinary Studies, 2018)
AbstractStudents are adult learners who are required to be independent in learning. Along with the rapid and massive development of the times, in self-directed learning students are currently facilitated by the availability of technology. So in this era of digital literacy becomes important provisions in student independent learning. In this study, the author will examine digital literacy and self-directed learning independent learning abilities among students of third-year English Education IAIN Surakarta. This research leads to qualitative research. The results of the study note that, to complete the assignments of the lecturers, many students use the internet as a source of learning. In addition they realize that they have implemented independent learning (SDL) in their daily lives. Balanced by their ability to digitally literate, the process of independent learning increasingly adds to the learning outcomes.Keywords: Digital literacy, self-directed learning